Cochlear Duct Length: Are We Giving It Adequate Importance?. (23rd August 2013) - Grover, Mohnish; Mishra, Prakash; Gupta, Gaurav; Jangid, Manoj
Abstract : Objectives: 1) Calculate radiologically length of cochlear duct in children with congenital bilateral profound sensorineural hearing loss. 2) Analyze above calculation to decide about length of electrode array of cochlear implant. 3) Implement this calculation as part of mandatory workup for cochlear implantation. Methods: Prospective study conducted over 18 months to study high‐resolution computed tomography (HRCT) temporal bone of children less than 6 years old being evaluated for cochlear implant at SMS Medical College and Hospital, Jaipur, India. Minimum intensity projection reconstruction cuts were made to calculate largest distance from round window to lateral wall of cochlea (A). Cochlear duct length (CDL) was calculated by: CDL = 4.16A – 3.98. Results: HRCT temporal bone of 124 patients with hearing loss were analyzed. Twenty patients were excluded in view of vestibulocochlear anomaly. Overall average of A was found to be 8.12 mm (7.7mm to 9.2mm). Mean cochlear duct length was calculated to be 29.8 mm (28mm to 34.3 mm). Conclusions: This study revealed that the length of cochlea is smaller in Asian population. The variability of cochlear length also needs to be taken into consideration before putting in a fixed length cochlear implant in every patient. In view of this we propose that cochlear duct length should be calculated in every patient preoperatively.